1996
DOI: 10.1113/jphysiol.1996.sp021185
|View full text |Cite
|
Sign up to set email alerts
|

Activation of L‐arginine transport (system y+) and nitric oxide synthase by elevated glucose and insulin in human endothelial cells.

Abstract: 1. Modulation of L-arginine transport (system y+) and release of nitric oxide (NO) and prostacyclin (PGI2) by elevated glucose and insulin were investigated in human cultured umbilical vein endothelial cells. 2. Elevated glucose induced a time-(6-12 h) and concentration-dependent stimulation of L-arginine transport, which was reversible and associated with a 3-fold increase in intracellular cGMP accumulation (index of NO synthesis) and 75 % decrease in PGI2 production. 3. Elevated glucose had no effect on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
131
4
4

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(168 citation statements)
references
References 22 publications
28
131
4
4
Order By: Relevance
“…Moreover, we have demonstrated that the effect of the eNOS substrate L-arginine on NO release and vasodilation is enhanced by D-glucose in a concentration-dependent manner. This finding is in accordance with a report of Sobrevia et al [39] which reported that D-glucose potentiates the uptake of L-arginine in vascular endothelial cells via the sodium-independent y + -transport system. However, this mechanism of eNOS activation may only be relevant at high levels of of L-arginine, and is unlikely to occur at physiological plasma concentrations with baseline levels of about 90 µmol/l and post-prandial peaks of about 130 µmol/l [40,41].…”
Section: Additive Effects Of D-glucose and Insulin On Nitric Oxide Fosupporting
confidence: 94%
“…Moreover, we have demonstrated that the effect of the eNOS substrate L-arginine on NO release and vasodilation is enhanced by D-glucose in a concentration-dependent manner. This finding is in accordance with a report of Sobrevia et al [39] which reported that D-glucose potentiates the uptake of L-arginine in vascular endothelial cells via the sodium-independent y + -transport system. However, this mechanism of eNOS activation may only be relevant at high levels of of L-arginine, and is unlikely to occur at physiological plasma concentrations with baseline levels of about 90 µmol/l and post-prandial peaks of about 130 µmol/l [40,41].…”
Section: Additive Effects Of D-glucose and Insulin On Nitric Oxide Fosupporting
confidence: 94%
“…Insulin induces a dose and time-dependent vasodilation in the peripheral arteries [9,10,11] by a endothelium-dependent mechanism including the L-arginine-nitric oxide pathway [12,13] and the sympathetic nervous system [13]. Insulin induces vasodilation also in myocardial vasculature in healthy humans [14].…”
mentioning
confidence: 99%
“…Their medical history, physical examination, and routine laboratory tests showed no evidence of diabetes, cardiovascular or other diseases. Their age was 22.5 ± 0.9 years (M ± SE, range 19-28), body mass index 22.8 ± 1.0 kg/m 2 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29), serum cholesterol 5.0 ± 0.4 mmol/l (3.9-7.1), and HbA 1c 5.0 ± 0.1% (4.5-5.3). None of the subjects took any medication for at least 2 weeks before the study.…”
Section: Methodsmentioning
confidence: 99%
“…7,16,22,23 Others observed no effect on NO production 18 or even the opposite, namely that hyperglycaemia may in fact stimulate the production of NO. 24,25 There is no doubt that the induction of systemic hyperglycaemia in healthy lean and obese men results in increases of leg blood flow. 26 In view of the literature findings discussed, it seems that hyperglycaemia acutely induces vasodilation in the peripheral resistance vessels of the forearm and leg.…”
Section: Does Glucose Induce Vasodilation or Vasoconstriction?mentioning
confidence: 99%
See 1 more Smart Citation